Fatigue Behavior of High Strength Steel S890Q Containing Thermally Cut Straight Edges. (2016) - Cicero, S.; García, T.; Álvarez, J.A.; Bannister, A.; Klimpel, A.; Martín-Meizoso, A.; Aldazabal, J.
Abstract: This paper evaluates the effect of different thermal cutting methods on the fatigue life of high strength steel S890Q. The investigation covers flame, plasma and laser cutting methodologies, and specimens with rectangular sections and cut straight edges. The experimental program is composed of 30 specimens that were conducted to failure by applying fatigue cycles with a stress ratio (R) of 0.1 in a high frequency testing machine. The resultant best-fit S-N curves have been compared, revealing a better performance for laser cut straight edges. Moreover, the corresponding Eurocode 3 FAT class has been derived for each of the three cutting methods, resulting in FAT160 in all cases. This suggests that the use Eurocode 3 FAT125, which is the fatigue class currently provided for flame cut straight edges, is an overconservative assumption for thermally cut straight edges in steel S890Q, regardless of the thermal cutting technique being used (flame, laser or plasma).